Glyphosate-Dependent Inhibition of Photosynthesis in Willow - Gomes, Marcelo P.; Le Manac’h, Sarah G.; Hénault-Ethier, Louise; Labrecque, Michel; Lucotte, Marc; Juneau, Philippe (Frontiers in Plant Science, 2017)
We studied the physiological mechanisms involved in the deleterious effects of a glyphosate-based herbicide (Factor® 540) on photosynthesis and related physiological processes of willow (Salix miyabeana cultivar SX64) plants. Sixty-day-old plants grown under greenhouse conditions were sprayed with different rates (0, 1.4, 2.1 and 2.8 kg a.e ha-1) of the commercial glyphosate formulated salt Factor® 540. Evaluations were performed at 0, 6, 24, 48 and 72 h after herbicide exposure. We established that the herbicide decreases chlorophyll, carotenoid and plastoquinone contents, and promotes changes in the photosynthetic apparatus leading to decreased photochemistry which results in peroxide (H2O2) accumulation. H2O2 accumulation triggers proline production which can be associated with oxidative protection, NADP+ recovery and shikimate pathway stimulation. Ascorbate peroxidase (APX) and glutathione peroxidase (GPX) appeared to be the main peroxidases involved in the H2O2 scavenging. In addition to promoting decreases of the activity of the antioxidant enzymes, the herbicide induced decreases in ascorbate pool. For the first time, a glyphosate-based herbicide mode of action interconnecting its effects on shikimate pathway, photosynthetic process and oxidative events in plants is presented.